Identifikasi Bakteri pada Ikan Pindang Tongkol (Euthynnus affinis) di Pasar Tradisional Semarapura, Klungkung, Bali - Kusumaningsih, Purwaningtyas; Diaris, Ni Made (Jurnal Veteriner, 2021)
Mackerel tuna (Euthynnus affinis) brine salting is a famous seafood product in Indonesia due to its good nutrition content. Bacterial contamination on this product may increase risk of foodborne diseases to happen, in addition to a decrease in quality and nutritionous value of the product. The main objective of this research was to identify bacteria contaminating the brine salting Mackerel tuna (Euthynnus affinis) sold in Tradisional Markets in Klungkung, Bali, Indonesia. Polymerase Chain Reaction (PCR) was apllied in the process of identification of bacterial contaminants. Samples were collected from 5 fish kiosks at the Tradisional market in Klungkung, Bali Indonesia. Each sample was cultured in Blood Agar or Nutrient Agar. Colonies with different morfology were selected, enriched in Tryptic Soy Broth (TSB), and their DNA was extracted before being amplified with 16S rRNA primers. This PCR products were then sequenced, and the results were compared with those available in the geneBank. Basic Local Alignment Search Tool was conducted with help of MEGA software version 6. Seven bacterial species were identified, and these included Serratia nematodiphila, Bacillus cereus, Shewanella seohaensis, Vibrio alginolyticus, Kurthia gibsonii, Enterobacter cloacae, and Staphylococcus sciuri. All but one Kurthia gibsonii are potensial pathogens in human. Staphylococcus sciuri is not commonly found in seafood. The present of such species in the mackerel tuna brine salting product was probably due to poor handling during the process and distribution.